2019
DOI: 10.1111/cei.13286
|View full text |Cite
|
Sign up to set email alerts
|

Novel multi-component vaccine approaches for Burkholderia pseudomallei

Abstract: Burkholderia pseudomallei is the causative agent of melioidosis. Historically believed to be a relatively rare human disease in tropical countries, a recent study estimated that, worldwide, there are approximately 165 000 human melioidosis cases per year, more than half of whom die. The bacterium is inherently resistant to many antibiotics and treatment of the disease is often protracted and ineffective. There is no licensed vaccine against melioidosis, but a vaccine is predicted to be of value if used in high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…To test this, we next compared the protective efficacy of the M9 OMV versus the live Bp82 strain (from which the OMVs are derived) in a comparator experimental immunization and challenge study. For these experiments, we tested the new M9 OMV formulation in C57Bl/6 mice since this strain has become the preferred rodent model for evaluation of B. pseudomallei vaccine candidates 5 . Mice were immunized subcutaneously twice, 3 weeks apart, with M9 OMVs or live Bp82 and challenged one month later with an aerosolized dose (8 x LD 50 ) of virulent B. pseudomallei strain K96243 that would achieve complete mortality in control mice.…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we next compared the protective efficacy of the M9 OMV versus the live Bp82 strain (from which the OMVs are derived) in a comparator experimental immunization and challenge study. For these experiments, we tested the new M9 OMV formulation in C57Bl/6 mice since this strain has become the preferred rodent model for evaluation of B. pseudomallei vaccine candidates 5 . Mice were immunized subcutaneously twice, 3 weeks apart, with M9 OMVs or live Bp82 and challenged one month later with an aerosolized dose (8 x LD 50 ) of virulent B. pseudomallei strain K96243 that would achieve complete mortality in control mice.…”
Section: Resultsmentioning
confidence: 99%
“…There are no melioidosis vaccines currently available for human use. Despite some vaccine candidates providing partial protection against melioidosis in murine models of infection, 134,135 few have been tested in nonhuman primates or humans. 136 However, antibody responses play a key role in protection against melioidosis 137 and CD8þ T cell responses are correlated with increased survival.…”
Section: Vaccinesmentioning
confidence: 99%
“…138 Encouragingly, these findings of a subunit vaccine 138 developed by Paul Brett and Mary Burtnick at the University of Nevada, Reno, have led to the first phase 1 clinical trial, due to commence in volunteer subjects with and without diabetes at Oxford University, United Kingdom in 2021 (Prof. S. Dunachie, personal communication). It is also worth mentioning that other conjugated vaccine candidates also show promise and an extensive review has recently been published by Morici et al 135 Modeling has already demonstrated that a melioidosis vaccine targeted at high-risk populations in endemic areas would be beneficial by reducing disease burden and be costeffective. 139…”
Section: Vaccinesmentioning
confidence: 99%
“…This review series also includes articles on bacterial pathogens, such as the Burkholderia species, which cause significant morbidity. Morici, Torres and Titball address progress in the development of vaccines for melioidosis, a bacterial disease which causes an estimated 165 000 human cases per year, with a mortality rate which can reach 40% where there are co‐morbidities, such as diabetes. This disease occurs in tropical areas of the globe, with a high incidence in northern Australia and South East Asia, where the disease is considered endemic.…”
mentioning
confidence: 99%